Tunneling nanotube formation promotes survival against 5‐fluorouracil in MCF‐7 breast cancer cells. Issue 1 (17th November 2021) - Kato, Kaylyn; Nguyen, Kim Tho; Decker, Carl W.; Silkwood, Kai H.; Eck, Sydney M.; Hernandez, Jeniffer B.; Garcia, Jerome; Han, Derick
Abstract : Tunneling nanotubes (TNTs) are F‐actin‐based open‐ended tubular extensions that form following stresses, such as nutritional deprivation and oxidative stress. The chemotherapy agent 5‐fluorouracil (5‐FU) represents a significant stressor to cancer cells and induces thymidine deficiency, a state similar to nutritional deprivation. However, the ability of 5‐FU to induce TNT formation in cancer cells and potentially enhance survival has not been explored. In this study, we examined whether 5‐FU can induce TNT formation in MCF‐7 breast cancer cells. Cytotoxic doses of 5‐FU (150–350 μm ) were observed to significantly induce TNT formation beginning at 24 h after exposure. TNTs formed following 5‐FU treatment probably originated as extensions of gap junctions as MCF‐7 cells detach from cell clusters. TNTs act as conduits for exchange of cellular components and we observed mitochondrial exchange through TNTs following 5‐FU treatment. 5‐FU‐induced TNT formation was inhibited by over 80% following treatment with the F‐actin‐depolymerizing agent, cytochalasin B (cytoB). The inhibition of TNTs by cytoB corresponded with increased 5‐FU‐induced cytotoxicity by 30–62% starting at 48 h, suggesting TNT formation aides in MCF‐7 cell survival against 5‐FU. Two other widely used chemotherapy agents, docetaxel and doxorubicin induced TNT formation at much lower levels than 5‐FU. Our work suggests that the therapeutic targeting of TNTs may increase 5‐FU chemotherapy efficacy and decrease drug resistance in cancer cells, and these findings merits further investigation. Abstract : Tunneling nanotubes (TNTs) are F‐actin–based tubular extensions that form following stress. Cytotoxic doses of 5‐fluorouracil (5‐FU) significantly induced TNT formation in MCF‐7 cells, which acted as conduits for mitochondrial exchange. The inhibition of TNTs by cytochalasin B increased 5‐FU cytotoxicity suggesting that the targeting of TNTs may increase 5‐FU efficacy in cancer cells.